Testing a model of personal attributes and emotions regarding physical activity and sedentary behaviour. Issue 5 (3rd September 2021) - Simonton, Kelly L.
ABSTRACT : The purpose of this study was to test a model of personal appraisals (distal) and emotions (proximal) as predictors of physical activity (PA) and sedentary behaviour using the Control Value Theory (CVT). Data was collected using a cross-sectional design and focused on college students ( N  = 345; M age  = 19.63, SD = 1.87) enrolled in a general education college course. The survey tools asked students about their perceptions of perceived control, value, enjoyment, boredom, and anxiety regarding physical activity. Students also reported their moderate-to-vigorous PA (MVPA) and sedentary time. Results showed all variables to be reliable ( α > .70) and confirmatory factor analysis supported factor structure. As hypothesised within CVT, control and value appraisals predicted enjoyment, boredom, and anxiety in students with one exception between value and enjoyment. However, 60%, 42%, and 42% of the variance were accounted for in each emotion, respectively. Enjoyment was a significant predictor of both PA and sedentary behaviour. Indirect relationships from control to PA and sedentary behaviour were also significant via enjoyment. Although indirect relationships were found between control value and behaviour via enjoyment, the effect size was minimal. In conclusion, discrete emotions represent motivational constructs that may help explain subjective experiences and volitional PA. Enjoyment was a predictor of one's PA behaviour and a deterrent to sedentary time. However, a greater number of emotions need exploration and may aid in filling some of the gaps understanding PA behaviour.